2019
DOI: 10.3390/molecules24193610
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Halogen Bonding Induced by Pentafluorosulfanyl Aryl Iodides: A Potential Group of Halogen Bond Donors in a Rational Drug Design

Abstract: The activation of halogen bonding by the substitution of the pentafluoro-λ6-sulfanyl (SF5) group was studied using a series of SF5-substituted iodobenzenes. The simulated electrostatic potential values of SF5-substituted iodobenzenes, the ab initio molecular orbital calculations of intermolecular interactions of SF5-substituted iodobenzenes with pyridine, and the 13C-NMR titration experiments of SF5-substituted iodobenzenes in the presence of pyridine or tetra (n-butyl) ammonium chloride (TBAC) indicated the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 93 publications
1
6
0
1
Order By: Relevance
“…[17][22] However, the attempt was unsuccessful and one speculation for the failure was the poor nucleophilicity of the aniline. To validate this hypothesis, we attempted the same reaction with 2-amino-5nitrobenzophenone as the nitro group has an electronic effect fairly close to that of the SF5 group (p = 0.68 [5] for SF5 and p = 0.78 [23] for NO2). The result was as postulated, unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…[17][22] However, the attempt was unsuccessful and one speculation for the failure was the poor nucleophilicity of the aniline. To validate this hypothesis, we attempted the same reaction with 2-amino-5nitrobenzophenone as the nitro group has an electronic effect fairly close to that of the SF5 group (p = 0.68 [5] for SF5 and p = 0.78 [23] for NO2). The result was as postulated, unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 68 Synthesis of (S)-meta-SF5 ostarine analogues 61 Scheme 69 Synthesis of (S)-para-SF5 ostarine analogues 61 Shibata et al investigated the effect of SF5-substitution in iodobenzenes on halogen bonding activation, using a combination of 13 C NMR experiments and ab initio molecular orbital calculations, using pyridine as halogen bonding acceptor. 62 The results indicated the following halogen bonding donor effectiveness: 3,5-bis-SF5-iodobenzene > o-SF5-substituted >> m-and p-SF5 substitutions, which did not activate the halogen bonding. Similar ortho-effect was confirmed -for comparison -on a series of NO2-substituted iodobenzenes.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Figure 8 The 2:1 halogen bonded complex between 3,5-bis-SF 5 -iodobenzene and DABCO 62 Togni et al reported the analysis of crystal structures of SF 5 -or SF 4 Cl containing molecules (such as those shown in Figure 9), which revealed that these groups are often surrounded by H or other F-atoms. 63 It was also shown that these compounds form a number of repeating structural motifs through contacts involving SF 5 groups, including different supramolecular dimers and infinite chains.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…As a result of such unique properties, aryl‐SF 5 compounds have attracted attention, and synthetic efforts towards their preparation have been the focus of intensive research [11] . Investigations on Ar−SF 5 span from applications as t Bu and CF 3 isosteres in medicinal chemistry, [10, 58] optoelectronic materials, [59] or agrochemicals, [60] to their ability to function as push‐pull fluoro‐ [61] and choromophores [62] . Before discussing Ar−SF 5 compounds, it is important to mention that the first syntheses of C−SF 5 compounds were reported in the 1950s by Cady and co‐workers (Scheme 25).…”
Section: Fluorination Levelmentioning
confidence: 99%